Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1097/ijg.0000000000000026
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fluctuations of Intraocular Pressure Before and After Selective Laser Trabeculoplasty in Normal-tension Glaucoma Patients

Abstract: SLT treatment was shown to significantly lower IOP and decrease IOP fluctuations during the nocturnal periods in NTG patients. These effects might be important to prevent the progression of NTG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 14 publications
3
34
0
3
Order By: Relevance
“…4 Since its introduction into clinical practice, SLT has been recognized as a useful treatment alternative for various types of glaucoma. [5][6][7] Several studies have reported the efficacy of SLT in treating open-angle glaucoma. However, the efficacy of SLT in reducing IOP varies substantially among studies.…”
mentioning
confidence: 99%
“…4 Since its introduction into clinical practice, SLT has been recognized as a useful treatment alternative for various types of glaucoma. [5][6][7] Several studies have reported the efficacy of SLT in treating open-angle glaucoma. However, the efficacy of SLT in reducing IOP varies substantially among studies.…”
mentioning
confidence: 99%
“…[34][35][36][37][38][39] In brief, the wireless CLS device was attached to one randomly selected eye of each subject, and an orbital patch containing a loop antenna was applied and connected to a portable recorder overnight. The CLS system is capable of recording a measurement every 5 minutes for a duration of 30 seconds, giving a total of 288 measurements over a 24-hour period.…”
Section: Continuous Iop Monitoringmentioning
confidence: 99%
“…The contact lens sensor (CLS) is a recently established device allowing 24-hour continuous IOP monitoring with no requirement of waking subjects up during the nocturnal sleep period. [34][35][36][37][38][39] We herein report the first evidence that shows the impact of apneahypopnea events on IOP values evaluated with overnight continuous monitoring using the CLS device in patients with OSAS.…”
mentioning
confidence: 99%
“…Die gleiche Studie fand aber auch, dass viele dieser Patienten zusätzlich Medikamente oder Operationen benötigten. Die SLT konnte den IOD signifikant senken und die IOD-Fluktuation während der Nacht bei Normaldruckglaukom verringern [32].…”
Section: Lasertrabekuloplastikunclassified